Strategi Peningkatan Produktivitas Sapi Potong Melalui Optimalisasi Pakan Konsentrat Di Perbauangan - Putri Sriwahyuni; Mita Purnama Sari; Elma Yanti Dewi; Anastasia Johananiel Maaseya Sitorus; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to evaluate strategies for increasing beef cattle productivity through optimizing concentrate feed based on local ingredients in Perbaungan, Serdang Bedagai Regency. Surveys and interviews were conducted to collect data regarding feeding patterns, costs and production efficiency. The research results show that concentrate feed, although more expensive than forage, provides higher efficiency in supporting daily weight gain in beef cattle. Local ingredients such as rice bran, palm oil cake and tofu dregs have great potential for use in concentrate formulations, thereby reducing costs and increasing the sustainability of livestock businesses. Optimal strategies include providing concentrate as needed, combining with forage, and managing feed stock. This optimization has been proven to be able to increase beef cattle. productivity and support national meat self-sufficiency efforts